2017
DOI: 10.11646/zootaxa.4250.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approaches for blood meal analysis and species identification of mosquitoes (Insecta: Diptera: Culicidae) in rural locations in southern England, United Kingdom

Abstract: Thirty-four species of Culicidae are present in the UK, of which 15 have been implicated as potential vectors of arthropod-borne viruses such as West Nile virus. Identification of mosquito feeding preferences is paramount to the understanding of vector-host-pathogen interactions which, in turn, would assist in the control of disease outbreaks. Results are presented on the application of DNA barcoding for vertebrate species identification in blood-fed female mosquitoes in rural locations. Blood-fed females (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 39 publications
1
40
1
Order By: Relevance
“…Some mosquito species that feed on multiple hosts can act as a "bridge" vector enabling transmission of a virus that normally replicates in birds being transmitted to humans and livestock. A number of previous studies have confirmed that mosquitoes feed on a range of livestock and wildlife (15)(16)(17)(18)(19). In the case of some mosquito species including Culiseta annulata and Anopheles messeae, they appear to feed exclusively on large ruminants.…”
Section: Mosquitoes and Mosquito-borne Diseasesmentioning
confidence: 92%
“…Some mosquito species that feed on multiple hosts can act as a "bridge" vector enabling transmission of a virus that normally replicates in birds being transmitted to humans and livestock. A number of previous studies have confirmed that mosquitoes feed on a range of livestock and wildlife (15)(16)(17)(18)(19). In the case of some mosquito species including Culiseta annulata and Anopheles messeae, they appear to feed exclusively on large ruminants.…”
Section: Mosquitoes and Mosquito-borne Diseasesmentioning
confidence: 92%
“…Due to improvements in sequencing technology, the Illumina NovaSeq consistently detected more metazoan taxa from seawater samples than did the MiSeq with an equivalent sequencing depth (Singer et al ., ), but it is more expensive. We also note here that MiSeq sequencing and bioinformatics can be outsourced to commercial companies or dedicated laboratories at reasonable (and decreasing) cost (Brandon‐Mong et al ., ; Hernandez‐Triana et al ., ; Kerley et al ., ). Overall, we recommend that researchers start with the MiSeq platform as it is suitable for most DNA metabarcoding studies with respect to sequencing accuracy, output and cost.…”
Section: Quantifying Species Abundance or Biomassmentioning
confidence: 99%
“…Although the study involved a small sample size, the results of the study give a clue on the prevailing vector-host-pathogen interactions in the area and hence may guide in planning disease outbreak control tools [2]. When resources allow, tests and analyses will be carried out on larger samples in the future.…”
Section: Blood Feeding Patterns and Anthropophilicmentioning
confidence: 99%
“…Understanding of mosquito behaviour related to host feeding preference is important in understanding of vector-host-pathogen interacttions and can facilitate the design and consolidation of effective vector control interventions in an area [1][2][3][4]. Identification of the blood meal taken by the vector is the most objective method of identifying its natural blood sources [5,6].…”
Section: Introductionmentioning
confidence: 99%